Low back pain: prevalence and associated risk factors among hospital staff - Karahan, Azize; Kav, Sultan; Abbasoglu, Aysel; Dogan, Nevin (Journal of advanced nursing, 2009)
Title.  Low back pain: prevalence and associated risk factors among hospital staff. Aim.  This paper is a report of a study conducted to describe the prevalence and risk factors for lower back pain amongst a variety of Turkish hospital workers including nurses, physicians, physical therapists, technicians, secretaries and hospital aides. Background.  Hospital workers experience more low back pain than many other groups, the incidence varies among countries. Work activities involving bending, twisting, frequent heavy lifting, awkward static posture and psychological stress are regarded as causal factors for many back injuries. Method.  A 44‐item questionnaire was completed by 1600 employees in six hospitals associated with one Turkish university using a cross‐sectional survey design. Data were collected over nine months from December 2005 to August 2006 and analysed using Chi square and multivariate logistic regression techniques. Findings.  Most respondents (65·8%) had experienced low back pain, with 61·3% reporting an occurrence within the last 12 months. The highest prevalence was reported by nurses (77·1%) and the lowest amongst secretaries (54·1%) and hospital aides (53·5%). In the majority of cases (78·3%), low back pain began after respondents started working in the hospital, 33·3% of respondents seeking medical care for ‘moderate’ low back pain while 53·8% (n = 143) had been diagnosed with a herniated lumbar disc. Age, female gender, smoking, occupation, perceived work stress and heavy lifting were statistically significant risk‐factors when multivariate logistic regression techniques were conducted (P < 0·05). Conclusion.  Preventive measures should be taken to reduce the risk of lower back pain, such as arranging proper rest periods, educational programmes to teach the proper use of body mechanics and smoking cessation programmes.